On the ideological constitution of the subject. Theodor Adorno and Louis Althusser - Matías Robles, Gustavo (Revista de Filosofía, 2018)
The aim of this paper is to carry on a parallel reading of the criticisms of the concept of subject carried out by Theodor Adorno and by Louis Althusser, from two very different theoretical traditions. This in order to show that: 1) their criticisms are based on the collapse of Hegelian Marxism and its idea of a subject of history, 2) that both try to unveil the ideological nature of the category of subject, and 3) that for that purpose they debate with the psychoanalytic tradition. This will allow me to shed light on the meeting points and the enormous divergences between both authors.